2010
DOI: 10.1592/phco.30.10.985
|View full text |Cite
|
Sign up to set email alerts
|

Increased Use of Acid‐Suppressing Drugs Before the Occurrence of Ischemic Events: A Potential Source of Confounding in Recent Observational Studies

Abstract: Use of acid-suppressing drugs increased before the occurrence of ischemic events regardless of the type (PPI or H(2)RA) or whether other drugs, such as clopidogrel, were concurrently administered. In addition, significant increases in overall drug use were observed during this time frame, suggesting that many patients exhibit warning signs before an acute hospitalization. Thus, PPI use before the occurrence of ischemic events may simply be a marker of unmeasured and uncontrolled confounding in observational st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 21 publications
2
17
0
Order By: Relevance
“…In our study, stroke was more frequently indicated in a PPI group than a control group, and patients using antiplatelet agents or anticoagulants, which may represent the cardiovascular or cerebrovascular comorbidities, were more frequently included in the PPI group. Therefore, the higher mortality rate of PEG in the PPI group may be associated with the higher rate of cardiovascular or cerebrovascular comorbidities in this group, because PPIs are frequently prescribed in these conditions 25. Secondly, the complications of PEG may be potentially increased by the use of PPI itself.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, stroke was more frequently indicated in a PPI group than a control group, and patients using antiplatelet agents or anticoagulants, which may represent the cardiovascular or cerebrovascular comorbidities, were more frequently included in the PPI group. Therefore, the higher mortality rate of PEG in the PPI group may be associated with the higher rate of cardiovascular or cerebrovascular comorbidities in this group, because PPIs are frequently prescribed in these conditions 25. Secondly, the complications of PEG may be potentially increased by the use of PPI itself.…”
Section: Discussionmentioning
confidence: 99%
“…PPI use may potentially increase the susceptibility to infection and pneumonia,18,19,20,21,22,23,24 which are common complications of PEG. Furthermore, PPI user in PEG patients may be associated with the higher rate of cardiovascular and cerebrovascular comorbidities 25. Therefore, it is hypothesized that PPI use in PEG patients might be associated with the adverse outcomes of PEG.…”
Section: Introductionmentioning
confidence: 99%
“…The use of PPIs itself has been reported to increase the risk for major adverse cardiovascular events and a biological mechanism linking PPIs and those events in the general population has been proposed [6,7]. In observational studies drug use in general has been reported to increase in the period before acute hospitalization due to a cardiac event suggesting no causal relationship between drug use and the adverse event but rather an effect of unmeasured confounding [8,9]. On the other hand, because of their potential similarity, prodromal symptoms of acute myocardial infarction (AMI) are sometimes interpreted as dyspepsia [10][11][12]; a mistake that represents a common cause of malpractice allegations in primary healthcare [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The potential source of confounding in observation studies associating PPIs with an MI risk may be an increased use of acid-suppressing drugs in the period before hospitalization, because prodromal symptoms of MI are sometimes misinterpreted as dyspepsia [42]. Indeed, a case-crossover study among 3490 MI cases demonstrated that PPI prescription appeared to increase the risk of MI by 70%.…”
Section: Controversy Regarding the Adverse Effect Of Ppis On Cardimentioning
confidence: 99%